MAIN CATEGORIES OF PEDAGOGY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article analyzes "pedagogy" as a separate science of education. As a separate branch of knowledge, pedagogy was isolated from philosophy. The merit of the pedagogy of Ancient Greece is that it laid the foundations for the formation of pedagogical theory and practice of teaching young people. Socrates, Plato, Aristotle are representatives of three generations of one school, which was based on the principle of free communication between teacher and students in an informal setting.